Evidence of Heritable Determinants of Decompression Sickness in Rats - Lautridou, J.; Buzzacott, Peter; Belhomme, M.; Dugrenot, E.; Lafère, P.; Balestra, C.; Guerrero, F. (Lippincott Williams & Wilkins, 2017)
Introduction Decompression sickness (DCS) is a complex and poorly understood systemic disease caused by inadequate desaturation after a decrease of ambient pressure. Strong variability between individuals is observed for DCS occurrence. This raises questions concerning factors that may be involved in the interindividual variability of DCS occurrence. This study aimed to experimentally assess the existence of heritable factors involved in DCS occurrence by selectively breeding individuals resistant to DCS from a population stock of Wistar rats. Methods Fifty-two male and 52 female Wistar rats were submitted to a simulated air dive known to reliably induce about 63% DCS: compression was performed at 100 kPa·min-1up to 1000 kPa absolute pressure before a 45-min long stay. Decompression was performed at 100 kPa·min-1with three decompression stops: 5 min at 200 kPa, 5 min at 160 kPa, and 10 min at 130 kPa. Animals were observed for 1 h to detect DCS symptoms. Individuals without DCS were selected and bred to create a new generation, subsequently subjected to the same hyperbaric protocol. This procedure was repeated up to the third generation of rats. Results As reported previously, this diving profile induced 67% of DCS, and 33% asymptomatic animals in the founding population. DCS/asymptomatic ratio was not initially different between sexes, although males were heavier than females. In three generations, the outcome of the dive significantly changed from 33% to 67% asymptomatic rats, for both sexes. Interestingly, survival in females increased sooner than in males. Conclusions This study offers evidence suggesting the inheritance of DCS resistance. Future research will focus on genetic and physiological comparisons between the initial strain and the new resistant population.